2018
DOI: 10.1136/bmjopen-2017-020938
|View full text |Cite
|
Sign up to set email alerts
|

Different predictors of pain severity across age and gender of a Chinese rural population: a cross-sectional survey

Abstract: ObjectivesTo investigate a 4-week period of pain prevalence and the risk factors of experiencing pain among a rural Chinese population sample. To explore the psychosocial and health condition predictors of pain severity and the interactions of age and gender with these factors in real-life situations among the general adult population in China.MethodsData were collected from a random multistage sample of 2052 participants (response rate=95%) in the rural areas of Liuyang, China. Visual analogue scale was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 88 publications
6
8
0
Order By: Relevance
“…Age significantly interacts with pain severity, especially people over 70 years old. This is consistent with a study from China [22]. Therefore, pain management should be modified and designed for different ages and genders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Age significantly interacts with pain severity, especially people over 70 years old. This is consistent with a study from China [22]. Therefore, pain management should be modified and designed for different ages and genders.…”
Section: Discussionsupporting
confidence: 89%
“…It is explained that older patients with chronic pain tend to develop depressive symptoms more often than older people in rural areas with non-chronic pain. The proportion of depressive symptoms in our sample is similar to that in the study from Lauren R [22]. Considering additional probably related factors of depression among the elderly, we found some positive associated factors mentioned above, such as pain location [19,21] and comorbidity [9].…”
Section: Discussionsupporting
confidence: 84%
“…This parallels the findings of previous research in a Chinese population that also found self-rated physical health was a predictor of pain severity. [ 21 ] Another study found that lower pain intensity among individuals with chronic pain was associated with better self-perception of health. [ 22 ] Interestingly, however, perceived mental health status was not associated with pain severity.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of studies identified potential predictors of pain, both in clinical trials and in population or cohort studies. Among population and cohort studies, evidence existed on the impact of sociodemographic characteristics, with females [26][27][28][29][30][31][32][33] and older people [6,27,28,31,32,34] reporting higher pain rates or severity. Also, people with lower education level and those unemployed had higher pain rates [35,36], but contrasting results were found with reference to socioeconomic position: in fact, Chen and colleagues found that people with a lower socioeconomic class had a more severe trajectory with regard to low back pain severity and persistence [37], whereas Elsharydah and colleagues found that higher median household income was associated with higher rate of complex regional pain syndrome type 1 [30].…”
Section: Introductionmentioning
confidence: 99%